مبدأ الكفاءة كآلية لتجويد الخدمة العمومية - رحموني, خديجة; حامدي, عصام (My University, 2023)
لقد تبنى المشرع مبدأ الكفاءة ضمنيا في الدستور وقد تمحور هذا المبدأ حول الكفاءة بمختلف صورها الاخلاقية الصحية والمهنية كما لمبدأ الكفاءة دور مهم في تحسين وتجويد الخدمة العمومية كما أنه قد كرس وشكلت له أجهزة لتدعيمه من خلال اللجنة الإدارية المتساوية الاعضاء ولجان الطعن واللجان التق.The legislator has implicitly adopted the principle of competence in the constitution. This principle revolved around competence in its various ethical, health and professional forms. The principle of competence also has an important role in improving and improving public service. It has also established and formed bodies for it to support it through equal members, appeal committees and technical committees through .
مذكرة ماستر
Keywords: : الكفاءة– الموظف – التوظيف – الخدمة: efficiency - employee - recruitment - service